The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1748-7161-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Relatively lower body mass index is associated with an excess of severe truncal asymmetry in healthy adolescents: Do white adipose tissue, leptin, hypothalamus and sympathetic nervous system influence truncal growth asymmetry?

Abstract: BMI is a surrogate measure for body fat and circulating leptin levels. The finding that girls with relatively lower BMI have significantly later menarche, and a significant excess of TAs, suggests a relation to energy homeostasis through the hypothalamus. The hypothesis we suggest for the pathogenesis of severe TA in girls and boys has the same mechanism as that proposed recently for AIS girls, namely: severe TAs are initiated by a genetically-determined selectively increased hypothalamic sensitivity (up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 64 publications
(42 reference statements)
3
34
0
2
Order By: Relevance
“…6 However, in the study of Qiu et al , 26 20% of circulation and enhance the leptin bioavailability in CSF. 37 , 44 Along with other studies, 6,9,10,14,16,45,46 AIS girls were found to have signifi cantly lower BMI and longer arm span than the healthy controls. This matches our observation on the change of sOB-R and FLI level in AIS girls.…”
Section: Discussionmentioning
confidence: 55%
“…6 However, in the study of Qiu et al , 26 20% of circulation and enhance the leptin bioavailability in CSF. 37 , 44 Along with other studies, 6,9,10,14,16,45,46 AIS girls were found to have signifi cantly lower BMI and longer arm span than the healthy controls. This matches our observation on the change of sOB-R and FLI level in AIS girls.…”
Section: Discussionmentioning
confidence: 55%
“…The maturation of the ocular and postural control systems coincides with the secondary rapid growth period. Some workers believe that not only the somatic nervous system is involved but the autonomic nervous system as well (Burwell, 2003;Grivas et al, 2009;Burwell et al, 2009). AIS in girls may then be the result from developmental disharmony expressed in spine and trunk between autonomic and somatic nervous systems.…”
Section: Neuromuscular Factorsmentioning
confidence: 99%
“…This is important because it highlights the impact of factors other than genetic make-up in developing scoliosis and has spawned the concept of epigenetics where factors other than genetics are considered to be major contributing factors (Grivas et al, 2002a(Grivas et al, , 2002b(Grivas et al, , 2006(Grivas et al, , 2007(Grivas et al, , 2008a(Grivas et al, , 2008b(Grivas et al, , 2009(Grivas et al, , 2001. Factors that might be considered must certainly include environmental conditions and their influence on spinal curve development and might present alternative treatment strategies (Hermus et al, 2007).…”
Section: The Promise Of Genetic Studiesmentioning
confidence: 99%